Immediate Renal Denervation After Acute Myocardial Infarction Mitigates the Progression of Heart Failure via the Modulation of IL-33/ST2 Signaling - Chen, Han; Wang, Rui; Li, Quan; Yin, Jiasheng; Ge, Zhenyi; Xu, Fei; Zang, Tongtong; Pei, Zhiqiang; Li, Chaofu; Shen, Li; Ge, Junbo (Frontiers in Cardiovascular Medicine, 2021)
Objective: Previous studies have demonstrated the protective effects of renal denervation (RDN) in pre-existing heart failure, but the effects of immediate RDN after acute myocardial infarction (AMI) on subsequent cardiac remodeling have not been reported. This study aimed to investigate the cardioprotective effects of immediate RDN after AMI and its underlying mechanism. Methods: AMI was induced by intracoronary gelatin sponge embolization in 14 Shanghai white pigs that were randomized to undergo either renal angiography (AMI+sham group) or RDN (AMI+RDN group) after 1 h of hemodynamic monitoring. Cardiac function of the two groups was measured at baseline, 1 h post-AMI and at the 1 month follow-up (1M-FU) by transthoracic echocardiography (TTE). Plasma NT-proBNP, soluble ST2 (sST2), norepinephrine (NE), and renin-angiotensin-aldosterone system activity were detected simultaneously. The renal cortex was harvested for NE measurement after the 1M-FU, and the renal arteries were stained with tyrosine hydroxylase for the evaluation of sympathetic activity. Heart tissues in the non-ischemic areas were collected to assess histological and molecular left ventricular (LV) remodeling by pathological staining, RT-PCR, and western blotting. Results: There was no difference in the hemodynamic stability or cardiac function between the two groups at baseline and 1 h post-AMI. Six pigs from each of the two groups completed the 1M-FU. TTE analysis revealed the improved cardiac function of immediate RDN in the AMI+RDN group and circulating NT-proBNP levels were lower than those in the AMI+sham group. Further analysis showed significantly less interstitial fibrosis in the remote non-ischemic myocardium after immediate RDN, together with decreased cardiomyocyte hypertrophy and inflammatory cell infiltration. sST2 levels in circulating and myocardial tissues of animals in the AMI+RDN group were significantly higher than those in the AMI+sham group, accompanied by corresponding alterations in IL-33/ST2 and downstream signaling. Conclusions: Immediate RDN can improve cardiac function and myocardial remodeling after AMI via modulation of IL-33/ST2 and downstream signaling.